Jamaica : managing political and economic change - Forbes, John D. (Washington : American Enterprise Institute for Public Policy Research, 1985)
This book describes the twenty-two years of Jamaican democratic political experience.
Includes bibliographical references: p. 53-54.
asm 22/01/2019
Loans
Keywords: Politics and government; Economic history; Jamaica